Tipografi pada Media 3 Dimensi sebagai Duta Pesan yang Efektif - Inda Ariesta (Humaniora, 2013)
Typography is now no longer considered as a science application on flat dimensions. Beyond the flat dimension, it is now often found not only in the form of dots, colors, lines, textures, Shapes and forms, but also thrived on typography users. Typography was used to deliver the message, through the formation of the language contained writings as title, subtitle, to captions on television media, but is now also used by other disciplines to deliver messages more readable than using other design elements. The purpose of this paper is to see the application of typography on the form, and how it can be delivered in addition to communicating the message letters by letters that can be strung into words, symbols, but in form. Typography was enjoyed so far for only words by words containing in newspapers, magazines, posters, flyers, brochures, etc., but now it can be enjoyed through out the media to the extent shapes, which also maximizes the delivery of messages. The character selecting skill which is adjusted in media and the message is one of new factors, because media controlling and materials are crossing disciplines of Visual Communication Design, which is in contact with the Product Design and Interior Design, which could work together to maximize the the message.